Interpersonal Communication of Parents with Children with Game Additions: Case Analysis of Online Mobile Legends Game Addiction - Naufal, Arifin Qois (Jogjakarta Communication Conference (JCC), 2023)
Addiction to online games is a problem that has received attention from the wider community. Currently, many studies only discuss on how to deal with addiction problems in children without knowing how the communication patterns of parents to their children who are addicted to online games, in this journal the authors want to discuss interpersonal communication between parents and children who are addicted to playing online games. Because the author believe that the initial problem of children becoming addicted to online games comes from improper interpersonal communication in the family between children and their parents. This study also discusses the digital parenting system used by parents to control the level of online game addiction in children. Because no parent wants their child to fall into excessive fun when playing online games, therefore a digital parenting system is needed to control or monitor children's digital activities. In this journal, author want to compare how 2 families with different economic and educational backgrounds control the same child who is addicted to playing online mobile legends games, but there are differences in the level of addiction in children from these 2 families, in a family 1 child experiences a moderate level of addiction. Whereas in the second family the children experienced a heavy addiction. This causes differences in the communication patterns of these 2 families in dealing with children who are addicted to playing mobile legends online games.